Mechanotransduction through adhesion molecules: Emerging roles in regulating the stem cell niche - Lim, Ryan; Banerjee, Avinanda; Biswas, Ritusree; Chari, Anana Nandakumar; Raghavan, Srikala (Frontiers in Cell and Developmental Biology, 2022)
Stem cells have been shown to play an important role in regenerative medicine due to their proliferative and differentiation potential. The challenge, however, lies in regulating and controlling their potential for this purpose. Stem cells are regulated by growth factors as well as an array of biochemical and mechanical signals. While the role of biochemical signals and growth factors in regulating stem cell homeostasis is well explored, the role of mechanical signals has only just starting to be investigated. Stem cells interact with their niche or to other stem cells via adhesion molecules that eventually transduce mechanical cues to maintain their homeostatic function. Here, we present a comprehensive review on our current understanding of the influence of the forces perceived by cell adhesion molecules on the regulation of stem cells. Additionally, we provide insights on how this deeper understanding of mechanobiology of stem cells has translated toward therapeutics.